Dose-response relationship between training load and anaerobic performance in female short-track speed skaters: A prospective cohort study - Huang, X.; Wang, G.; Zhen, L.; Zhao, J.; Gao, B. (Physiology & Behavior, 2022)
This study aimed to assess the dose-response relationship (DRR) between measures of training load (TL) and anaerobic performance in female short-track speed skaters. TL data from 22 female short-track speed skaters (mean ± SD; calendar age 20.7 ± 2.01 years, training length 4.18 ± 1.23 years, height 164.20 ± 5.53 cm, weight 52.00 ± 5.58 kg) was collected over a six week period. Participants completed two anaerobic capacity assessments (cycling parameters: total work, maximal anaerobic power [MAnP], power duration indices, maximal blood lactate, fatigue indices, and peak power output [PPO]) pre- and post-training, which included three tests (short-term, intermediate-term, and 120 s maximal anaerobic test). The mean weekly TL measures calculated were total distance, red zone (time spent > 85% of peak heart rate), Edwards training impulse (eTRIMP), Stagno training impulse (gTRIMP), Lucia training impulse, and session ratings of perceived exertion. The gTRIMP identified a curvilinear relationship and explained 79% and 63% of the variance in changes of MAnPi and PPO (R2 = 0.79, 95%CI = 0.64 to 1.00, turn point 621AU; R2 = 0.63, 95%CI = 0.27 to 1.00, turn point 633AU, respectively). Likewise, The eTRIMP identified a curvilinear relationship and explained 62% and 54% of the variance in changes of MAnPi and PPO (R2 = 0.62, 95%CI = 0.11 to 1.00, turn point 485AU; R2 = 0.54, 95%CI = 0.07 to 1.00, turn point 515AU, respectively). All other variables exhibited a DRR below moderate. This study investigated a TL strategy to improve the speed endurance of female short-track speed skaters and suggested the superiority of gTRIMP and eTRIMP methods of internal TL.